EGFR and PI3K pathway activities might guide drug repurposing in HPV-negative head and neck cancers - Mock, Andreas; Plath, Michaela; Moratin, Julius; Tapken, Maria Johanna; Jäger, Dirk; Krauß, Jürgen; Fröhling, Stefan; Heß, Jochen; Plath, Karim (Frontiers in oncology, 2021)
carcinomas (HNSCC), their impact on oncogenic signaling and cancer drug sensitivities remains elusive. To determine their consequences on the transcriptional network, pathway activities of EGFR, PI3K and 12 additional oncogenic pathways were inferred in 498 HNSCC samples of The Cancer Genome Atlas using PROGENy. More than half of HPV-negative HNSCC showed a pathway activation in EGFR or PI3K. An amplification in EGFR and a mutation in PI3KCA resulted in a significantly higher activity of the respective pathway (p=0.017 and p=0.007). Interestingly, both pathway activations could only be explained by genetic alterations in less than 25% of cases indicating additional molecular events involved in the downstream signaling. Suitable in vitro pathway models could be identified in a published drug screen of 45 HPV-negative HNSCC cell lines. An active EGFR pathway was predictive for the response to the PI3K inhibitor buparlisib (p=6.36E-03) and an inactive EGFR and PI3K pathway was associated with efficacy of the BCL inhibitor navitoclax (p=9.26E-03). In addition an inactive PI3K pathway correlated with a response to multiple HDAC inhibitors. These findings require validation in preclinical models and clinical studies.